2009
DOI: 10.1590/s1677-55382009000300008
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 in congenital ureteropelvic junction obstruction: diagnosis and follow-up

Abstract: TGF-beta1 is a cytokine leading to renal fibrosis. The measurement of urinary TGF-beta1 could become a useful tool for the diagnosis of obstructive hydronephrosis and the evaluation of the parenchyma function status, pre and postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 28 publications
0
27
0
3
Order By: Relevance
“…High pressure in upper urinary tract in hydronephrosis and obstruction cases causes various molecular and histopathological changes and TGF-b1 increase by stimulating the RAA system and inflammation. 28,29 TGF-b1 isolated in serum in UPO cases were never before utilized, examined in this study for the first time, and detected in high levels in study groups. In this study, urine TGF-b 1 levels of both groups with UPO were seen to be statistically higher compared to the other groups (p < 0.05) while the kidneys were under hydronephrotic monitoring both USG and macroscopically during the exploration made while terminating the experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High pressure in upper urinary tract in hydronephrosis and obstruction cases causes various molecular and histopathological changes and TGF-b1 increase by stimulating the RAA system and inflammation. 28,29 TGF-b1 isolated in serum in UPO cases were never before utilized, examined in this study for the first time, and detected in high levels in study groups. In this study, urine TGF-b 1 levels of both groups with UPO were seen to be statistically higher compared to the other groups (p < 0.05) while the kidneys were under hydronephrotic monitoring both USG and macroscopically during the exploration made while terminating the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…While Merriki and Sager's studies found a higher urinary TGF-b 1 in children with UPO, these levels dropped after surgical treatment or spontaneous recovery. 28,29 AP diameters and renal ARI measurements were also utilized in our study in order to support the diagnostic accuracy of USG. The aim of this study is to constitute a reference for future studies by determining the average ARI values of standard rats and the ones induced with UPO in medical literature (ARI 0 ¼ 0.49 ± 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…Murakumo et al emphasized the importance of a multifaceted approach combining neurogenic and myogenic theories in understanding the etiopathogenesis of intrinsic UPJ obstruction (13). A recent non-invasive study, which focused on the measuring urinary TGF-β 1 in children with congenital UPJ obstruction confi rmed this urinary cytokine as a useful tool for the diagnosis and follow-up of UPJ obstruction (14).…”
Section: Discussionmentioning
confidence: 99%
“…Öte yandan kronik fazda ise, hidronefroz, renal atrofi, böbrek ağırlığında azalma, intertisyel fibrozis ve böbrek fonksiyon bozukluğu gelişmektedir (24) . Deneysel ve klinik çalışmalar (1,3,6,10,16,27,30) ; nefropatiye neden olan başlıca faktörle-rin glomerüler dinamikleri ve tübüler fonksiyonları etkileyen çeşitli vazoaktif peptidler ve bunların neden olduğu apopitotik mekanizmalar olduğunu gös-termiştir.…”
Section: Discussionunclassified
“…Bu histopatolojik değişikliklerden de renal kan akı-mının azalmasına yani iskemiye bağlı olarak üretimi artan bazı mediatörlerin ve serbest oksijen radikallerinin sorumlu olduğu gösterilmiştir (1,3,27,30) . Literatür-de tam veya kısmi ÜPB tıkanıklığında biyokimyasal, ultrastrüktürel ve fonksiyonel parametreler açısından karşı taraf böbrekte oluşan yanıtı inceleyen birkaç ça-lışma (2,7,26,32,33) vardır.…”
Section: Introductionunclassified